Consumers' Willingness to Pay for Health Benefits in Food Products: A Meta‐Analysis. (31st August 2017) - Dolgopolova, Irina; Teuber, Ramona
Abstract: This article analyzes the existing literature on consumers' marginal willingness to pay (MWTP) for health benefits in food products. Results indicate that the presence of a health claim does not only increase MWTP for health benefits in foods but also reduces heterogeneity among MWTP estimates. Hypothetical methods significantly positively affect MWTP. The most popular product category "dairy" negatively influences MWTP. The popular health claim of "lowering cholesterol" has a significantly positive influence on MWTP. In addition, our review highlights that existing studies significantly differ in their setup, which renders the inference of clear‐cut conclusions rather problematic.